COVID‐19, nausea, and vomiting. Issue 3 (5th October 2020) - Andrews, Paul L R; Cai, Weigang; Rudd, John A; Sanger, Gareth J
Abstract: Exclusion of nausea (N) and vomiting (V) from detailed consideration as symptoms of COVID‐19 is surprising as N can be an early presenting symptom. We examined the incidence of NV during infection before defining potential mechanisms. We estimate that the overall incidence of nausea (median 10.5%), although variable, is comparable with diarrhea. Poor definition of N, confusion with appetite loss, and reporting of N and/or V as a single entity may contribute to reporting variability and likely underestimation. We propose that emetic mechanisms are activated by mediators released from the intestinal epithelium by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) modulate vagal afferents projecting to the brainstem and after entry into the blood, activate the area postrema (AP) also implicated in anorexia. The receptor for spike protein of SARS‐CoV‐2, angiotensin 2 converting enzyme (ACE2), and transmembrane protease serine (for viral entry) is expressed in upper gastrointestinal (GI) enterocytes, ACE2 is expressed on enteroendocrine cells (EECs), and SARS‐CoV‐2 infects enterocytes but not EECs (studies needed with native EECs). The resultant virus‐induced release of epithelial mediators due to exocytosis, inflammation, and apoptosis provides the peripheral and central emetic drives. Additionally, data from SARS‐CoV‐2 show an increase in plasma angiotensin II (consequent on SARS‐CoV‐2/ACE2 interaction), a centrally (AP) acting emetic, providing a further potential mechanism in COVID‐19. Viral invasion of the dorsal brainstem is also a possibility but more likely in delayed onset symptoms. Overall, greater attention must be given to nausea as an early symptom of COVID‐19 and for the insights provided into the GI effects of SARS‐CoV‐2.